Cavity nucleation and growth in Cu–Zn–Al irradiated with Cu+ ions at different temperatures - Zelaya, Eugenia (2010)
The effects of high dose ion irradiation in beta Cu–Zn–Al were investigated between room temperature and 150ºC. Single crystal samples with surface normal close to [001]beta were irradiated with 300 keV Cu+ ions. Microstructural changes were characterized using transmission electron microscopy. Irradiation induced cavities located on the surface exposed to the irradiation were observed. The morphology, size and density distribution of these cavities were analyzed as a function of different irradiation conditions. The shape and location of the cavities with respect to the irradiation surface were not affected by irradiation temperature or irradiation dose. Instead, the cavity size distribution showed a bi-modal shape for a dose of 15 dpa, regardless of irradiation temperature. For a dose of 30 dpa the bi-modal distribution was only observed after room temperature irradiation. The diffusion effects of vacancies produced by irradiation are analyzed in shape memory Cu–Zn–Al alloys, which main characteristic is the diffusionless martensitic transformation. Particularly, the cavity size distributions were analyzed in terms of nucleation, growth and coalescence.